Balancing Fund and Inclusive Economic Growth: East Java Provincial Study - Cahayati, Nila; Ariestiningtyas, Dewanti Rahma; Purnamasari, Vidya (KnE Social Sciences, 2024)
One of the policies adopted by the government in development, especially in developing countries, is inclusive economic growth. This study examines how the effect of equalization funds as the main variables, as well as GDP per capita and open unemployment as control variables, on the Inclusive Economic Development Index (IDEI) as a proxy for inclusive economic growth. This research was conducted in 38 regencies/cities in East Java, in the period 2014-2020, using the PVECM Model as an analysis tool. In addition, this research also provides strategies and policy formulations in an effort to increase inclusive economic growth. The results show that in the long-term DAU and GDP per capita have a significant positive effect on inclusive development. Meanwhile, in the short term, DAK and GDP per capita have a positive insignificant effect. It can be concluded that the balancing fund supports inclusive economic development in East Java. Keywords: intergovernmental transfer funds, inclusive economic development index, inclusive economic growth